Inferior Vena Caval Syndrom in Paraaortic Metastastic Lession of Ovarian Dysgerminoma in Pregnancy Manage with Chemotherapy : a Case Report - Madona Utami Dewi; Syamel Muhammad (Andalas Obstetrics And Gynecology Journal, 2020)
Background : Inferior caval syndrom is a rare case. It can caused by compresssion of the tumor mass and paraaortic metastastasis lession of ovarian dysgerminoma. Dysgerminoma is one of the most common germ cell tumor, approximately 3-5% of all ovarian cancers.1 Rate of dysgerminoma metastasis to lymph node is around 28%. In all type of germ cell, dysgerminoma has higher insidens to lymph node metastasis compare to the others. The first level of lymph node metastsis is paraaortic lymph node. However, the insidens is unknown because there is no research about it yet.2,3 Dysgerminoma frequently in young age, less then 30 years. The exact etiology of dysgerminomas has not been determined, although recent molecular studies have implicated loss function of potential tumor suppressor gene TRC8/RNF139, abnormality of Y chromosome and gonadal dysgenesis.4 The problem arises when dysgerminoma is diagnosed in pregnancy woman as clinically has inferior vena cava syndrom sign and symptoms which acquired efective and fast management.Objective : Discuss inferior caval syndrom as effect of compression by tumor mass, metastasis tumor lesion and chemotherapy management in dysgerminoma with pregnancyCase Report : Patient 32 years old admitted to M. Djamil central general hospital referred from Batusangkar hospital with diagnosis G3P2A0L2 25-26 weeks of preterm pregnancy + dysgerminoma + obs. Dyspnue. Patient has symptoms dispnue, exercise intolerance, oedem extremity. Physical examination : blood pressure was 100/70 mmHg, HR 120 dpm, RR 35 bpm, T 37 C. Abdomen : uterus fundal was palpated 2 fingers above umbilical, ballotement (+), FHR 150-158 bpm. Genitalia : I V/U normal, vaginal bleeding (-), oedem extremity +/+. From ultrasonography found dysgerminoma ovary with compression to inferior vena cava and paraaortic metastatic. Patient was diagnosed with dispnue ec. inferior vena cava syndrom caused by compression of tumor mass + paraaortic lymph node metastasis lession of ovarian dysgerminoma on G3P2A0L2 25-26 weeks of preterm pregnancy. Patient was managed by BEP chemotherapy and symptom was dissapeared. Patient was admitted to M. Djamil again with 34-35 weeks of preterm pregnancy in active phase of first stage. Because obtructed of labor patient was decide to performed LSCS. Female baby was born 1800 gram, baby’s length was 45 cm, A/S 7/8, there is no congenital anomaly. Patient was followed up 1 month after surgery, there is no symptoms, but fromUltrasonograhy found corpus metastasis and CT scan impressed paraaortic lymph node metastasis + copus metastasis. Chemotherapy was continue one month after caesarean section. She was completed 4 cycles chemothrapy and the disease was cureable.Conclusion : Caval syndrom is a rare case and fatal, caused by direct compression of dysgerminoma mass and paraaortic lymph node metastasis. Diagnosis of dysgerminoma is anatomy pathology diagnose. Management of dysgerminoma is surgical staging and 3-4 cycle of chemoterapy with BEP regimen. Chemoterapy with BEP (Bleomisin-Etopuside-Cisplatin) is safe to performed at second trimester with inferior vena cava syndrom ec paraaorta lymph nodes metastasis.          Dysgerminoma has a good response to chemotherapy with survival rate 96%Keywords: Caval syndrom, lymph node paraaortic metastatic